2013
DOI: 10.1002/asia.201301270
|View full text |Cite
|
Sign up to set email alerts
|

Masked Thiol Sugars: Chemical Behavior and Synthetic Applications of S‐Glycopyranosyl‐N‐monoalkyl Dithiocarbamates

Abstract: The chemical behavior of S-glycopyranosyl-N-monoalkyl dithiocarbamates (DTCs) as masked 1-glycosyl thiols, easily prepared by the nucleophilic displacement of 1-halo sugars with dithiocarbamate salts of primary amines, has been studied and synthetically exploited. This behavior relies on the abstraction of the proton of the carbamate functionality that allows controlled access to thiolate sugar intermediates. The basic character of the DTC salts used as reagents leads to thiolates that evolve in situ to symmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…We made another attempt to glucosylate 8 with 7a using K 3 PO 4 as an alternative base to K 2 CO 3 . O -Glycosylation products 6a and 19a were detected in the crude mixture; however, the disulfide 20 was unexpectedly formed. Additionally, the polarity among the starting material 8 and products 6a , 19a , and disulfide 20 were close, thus complicating reaction monitoring (entry 4).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…We made another attempt to glucosylate 8 with 7a using K 3 PO 4 as an alternative base to K 2 CO 3 . O -Glycosylation products 6a and 19a were detected in the crude mixture; however, the disulfide 20 was unexpectedly formed. Additionally, the polarity among the starting material 8 and products 6a , 19a , and disulfide 20 were close, thus complicating reaction monitoring (entry 4).…”
Section: Resultsmentioning
confidence: 92%
“…The extract was washed with brine (10 mL) and concentrated in vacuo. The residue was purified by column chromatography ( n -hexane/EtOAc = 3:1) to give a pale brown amorphous residue (211 mg) including N -acetyl-3-(2,3,4,6-tetra- O -acetyl-β- d -glucopyranosyloxy)-1 H -indol-2-yl 2,3,4,6-tetra- O -acetyl-1-thio-β- d -glucopyranoside ( 6a , 62 mg, 71 μmol, 19%), 3-(2,3,4,6-tetra- O -acetyl-β- d -glucopyranosyloxy)-1 H -indol-2-yl 2,3,4,6-tetra- O -acetyl-1-thio-β- d -glucopyranoside ( 19a , 83.0 mg, 101 μmol, 27%), and bis­(2,3,4,6-tetra- O -acetyl-β- d -glucopyranosyl) disulfide ( 20 , 66 mg, 91 μmol, 25%). Yields of 6a , 19a , and 20 were estimated from the 1 H NMR spectrum (600 MHz) of the mixture.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Besides, in 2014, Megia-Fernandez et al [90] reported the ring-opening reaction of a cyclic sulphate mediated by a thioaldose, as a key reaction for the synthesis of thiodisaccharides. Like cyclic sulphamidates, cyclic sulphates proved to be versatile synthons as epoxide equivalents in organic synthesis.…”
Section: Ring-opening Reactions: Aziridines Sulphamidates and Sulphates As Substratesmentioning
confidence: 99%
“…Besides, in 2014, Megia‐Fernandez et al [90] . reported the ring‐opening reaction of a cyclic sulphate mediated by a thioaldose, as a key reaction for the synthesis of thiodisaccharides.…”
Section: General Strategies For the Access To Thiodisaccharides: The Hexnac Challengementioning
confidence: 99%